Congenital Cataract: Morphology and Management - Humaira Fawad, Sana Nadeem, Muhammad Ayub (Pakistan Journal of Ophthalmology, 2018)
Purpose: To evaluate the morphology of congenital cataracts presenting to us and their subsequent surgical management and visual rehabilitation. Material and Methods: A total of 46 eyes of 28 patients in the age range from 3 months to 25 years with unilateral or bilateral congenital cataract (diagnosed at any age), with no other associated ocular pathology of the anterior or posterior segment, no history or features of trauma, and without systemic or syndromic associations, presenting to the Department of Ophthalmology, Holy Family Hospital, Rawalpindi between 1st January, 2012 to 30th September, 2012 were included in this prospective, interventional study. Results: The most common morphological type of isolated congenital cataract found in our study was lamellar cataract in 12 eyes (26.1%), and total white cataract also in 12 eyes (26.1%), followed by isolated blue dot cataract in 3 eyes (6.5%). Mixed morphologies were found in 13 (28.2%) eyes. Pre-operative visual acuity was better than 6/18 in 13 (28.3%) eyes, less than 6/18 in 15 (32.6%) eyes, and unrecordable in 18 (39.1%) eyes. Best corrected visual outcome was significantly improved, with a visual acuity achieved better than 6/18 in 25 (54.3%) eyes, less than 6/18 in 5 (10.9%) eyes and unrecordable in 16 (34.8%) eyes. (p= 0.000) The minimum follow up was 3 months and maximum follow up was 15 months. Conclusions: Isolated lamellar and total white cataracts are the common morphologies of congenital cataract found in our study. Good visual outcome can be achieved with early surgical intervention and appropriate visual rehabilitation.